Pengaruh Pelayanan Informasi Obat (PIO) terhadap Penurunan Intensitas Nyeri pada Pasien Swamedikasi di Banyumas - Thariq Ahmad Thorir; Alfarid Kurnialandi; Wahyu Utaminingrum; Didik Setiawan (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Pain is health problem that affect human quality of life and often treated through self-medication, which possess risk in medication error. Drug information services take a role to avoid the medication errors, yet the implementation is far from optimal. Therefore, a study was conducted to overview the effectiveness of drug information services to reduce the pain intensity in Banyumas. The study used quasi experimental research with pretest-posttest design. The population was self-medication patients with pain symptom in 10 pharmacies in Banyumas. The sample consist of 200 respondents, including the intervention and control groups. The data was analyzed through univariate and bivariate (Mann-Whitney test). After self-medication was given, the average pain score in intervention group (given PIO) was 4.6 and the control group (did not given PIO) was 3.59 with p-value of 0.00 (α ≤ 0.05) indicating significant difference between two groups. This finding highlights the importance of drug information services by pharmacist to reduce the pain intensity and increase the treatment effectiveness among the self-medicated patients.